Epitheliotropic T-cell lymphoma in Syrian Hamster (Mesocricetus auratus) - Vetter, JR; Maidana, LG; De Oliveira, TES; Méndez-Morán, DN; Dacak, DA; Heurich-Suárez, GM (Journal of the Hellenic Veterinary Medical Society, 2024)
Lymphomas are neoplasms characterized by the clonal proliferation of malignant lymphocytes, are considered one of the most common tumors recognized in hamsters. The objective of the present work is to describe a case of cutaneous T-cell lymphoma (CTCL) in a Syrian hamster kept as a pet in Paraguay, diagnosed by histopathological and immunohistochemical techniques. We report the case of a 1-year-old, male, pet Syrian Hamster (Mesocricetus auratus), that presented scabs, ulcers, erythema, crusting, and hyperkeratosis, with a case evolution of approximately 20 days. Days after the inspection the animal is found dead, and the body is subjected to post-mortem examinations. Histopathologic analysis with hematoxylin-eosin and inmunohistochemic assays for CD3 and CD79 lymphoid markers and ki-67 cell proliferation are performed on skin sections, confirming the diagnosis for cutaneous T-cell lymphoma. Clinical signs and skin lesions coincide with cited literature, and confirmation through inmunohistochemical assays offer a better diagnosis. To date, there is no known cause nor treatment for cutaneous T-cell lymphoma in hamsters, and euthanasia is considered for animal welfare.